HUBUNGAN KOORDINASI MATA TANGAN DAN POWER OTOT LENGAN BAHU TERHADAP KEMAMPUAN PASSING ATAS TEAM BOLA VOLI PADA SISWA MAN 1 INDRAGIRI HILIR - sepriwandi, dedy; zainur, zainur; Wijayanti, ni putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aim of this reseasih was to determine the effect of eye coordination and shoulder arm strength on the passing capacity of the Man 1 Indragiri Hilir volleyball team. This is correlational research by comparing the results of measurements of two different variables to determine the level of correlation between these variables. The population in this reseasih was 6 students of class X, 6 students of class XI and 4 students of class XII. The data collection technique in this reseasih uses total sampling because it calculates a sample that is not too large, uses this correlation test and then tests the data using the normality test, product test of moment, correlation, variable normality test X₁ L₀maks (0.1194) <Ltabel (0.213), normality test for variables X₂ L₀maks (0.1556) <Label (0.213) and variable normality test Y L₀max (0.1414) <Label (0.213). In other words, normal data and research conclusions discuss where there is a correlation. The results of the correlation analysis state that there is a significant joint correlation between eye and hand coordination and arm and shoulder muscle power compared to the passivity of the voiball team in Indragiri Hilir Male 1 Students with r = (1,126)> rtable = (0,514). Key Words: Hand eye, strength of the shoulder arm. Muscle, top party, volleyball